1995
DOI: 10.1111/j.1399-0039.1995.tb02495.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of HLA class II polymorphism in Croatians

Abstract: HLA-class II polymorphisms have been studied in a population of 141 unrelated healthy Croatians using PCR amplification, followed by non-radioactive oligonucleotide hybridization. Thirty one DRB1, 8 DQA1, 13 DQB1 and 16 DPB1 alleles were found in the tested population. DRB1*1601, 0701, 1501, 0101 and 1104 are the most frequent alleles at the DRB1 locus. At the DQA1 locus two alleles predominate: DQA1*0501 and 0102, while the most frequent DQB1 allele is *0301. Analysis of HLA-DPB1 polymorphism showed that, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
5
17
0
Order By: Relevance
“…The DRB1*0701 and DRB1*1501 frequencies are similar to those observed in some other European populations such as the French (Caillat-Zucman et al, 1992) or Danish populations (Lindblom et al, 1992), but are higher than in Southern European populations such as the Croatian (Grubic et al, 1995), Bulgarian (Ivanova et al, 1996) and Romanian populations (Reed et al, 1992). In Ukrainians, these alleles are less frequent (Alexeev & Petranji, 1992).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The DRB1*0701 and DRB1*1501 frequencies are similar to those observed in some other European populations such as the French (Caillat-Zucman et al, 1992) or Danish populations (Lindblom et al, 1992), but are higher than in Southern European populations such as the Croatian (Grubic et al, 1995), Bulgarian (Ivanova et al, 1996) and Romanian populations (Reed et al, 1992). In Ukrainians, these alleles are less frequent (Alexeev & Petranji, 1992).…”
Section: Discussionsupporting
confidence: 75%
“…The high DRB1*0101 allele frequency distinguishes the Polish population from the neighbouring Ukrainian (Alexeev & Petranji, 1992) and German populations (Imanishi et al, 1992), and also from the Polish population from Wielkopolska (mid-western Poland), where it was observed at almost half the frequency found in our central Poland population (Jungerman et al, 1997). In other European populations, such as those of Croatia (Grubic et al, 1995), Romania (Reed et al, 1992), Bulgaria (Ivanova et al, 1996), Spain (Martinez-Laso et al, 1995) and Norway (Yasunaga et al, 1996), this allele is less frequent, although it is observed at a similar frequency in the Czech Republic, another neighbouring country (Cerna et al, 1992). A similar frequency of this allele has been observed in Denmark (Lindblom et al, 1992).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Since separate analyses of homozygotes and heterozygotes have not revealed any significant differences between the two groups in haplotype frequencies (data not shown), we assume that no gross misassignments have been perpetrated in either group. Moreover, several recent studies in which molecular class II gene typing has been applied to various smaller populations are revealing an HLA haplotype diversity that is much more extensive than expected (e.g., Bugawan and Erlich 1991;Grubic et al 1995;Trachtenberg et al 1995;Ivanova et al 1996).…”
Section: Haplotype Frequenciesmentioning
confidence: 99%
“…Harmful pathogens and toxins occur in a great variety in nature and an individual's ability to ¢ght an assault depends on its capacity to identify alien compounds and trigger an appropriate response. These defence systems are characterized by a high genetic diversity and complexity at loci that code for antigen or substrate a¤nities ( Grubic et al 1995;Trowsdale 1995;Parham & Ohta 1996;Zacharay et al 1996. b Cohen et al 1992Nakagawa et al 1993;Clot et al 1994;Nebert et al 1996;Nelson et al 1996;Parkinson 1996;Marez et al 1997.…”
Section: Genetic Variation and Function Of The Immune And Detoxicatiomentioning
confidence: 99%